Propuesta de una unidad en la enseñanza del inglés para propósitos generales y específicos - Valdivia, Jorge Eduardo; Poblete Ríos, Marcia (Colombian Applied Linguistics Journal, 2015)
This Project’s aim is to propose the creation of a unit in charge of renovating the traditional methodological conception of English for Specific Purposes (ESP) by combining the proposed learning outcomes of ESP courses, together with methodologies pointing to the achievement of learning outcomes proposed by English for General Purposes courses, as the use of foreign languages in the training process of specialists has been set as a mandatory condition for the contemporary professional. Then, the objective of this project is to create a unit in charge of the design of an English teaching plan common to all the programs of the Universidad de Atacama in Chile, which considers social and labor needs and which unifies the quality and modality of English courses offered by this institution. The impact this course would cause on the professionals of the Universidad de Atacama would constitute an extra tool for supporting the knowledge they have of their own specialty and for beneficiating the professionals’ performance, their professional projection, and their personal and social development. The study is exploratory, descriptive and quantitative at the time that it is transversal. It is expected that the resulting unit can be implemented in a near future.